Pre-service Teachers Statistical Reasoning based on Cognitive Style - Yusfita Yusuf; YL. Sukestiyarno (Didaktik Matematika, 2022)
The use of statistical concepts in real-life problems has become a challenge for students. This challenge is related to statistical reasoning (SR) ability which is influenced by several factors including cognitive style. Therefore, this research aims to understand the process of statistical reasoning from the perspective of cognitive style. A qualitative method was used and the subjects were students who are pre-service mathematics teachers. The instrument used were Group Embedded Figures Test (GEFT), statistical reasoning tests, as well as interview guidelines, and the data were analyzed using the qualitative descriptive method. The results showed statistical reasoning of the field independent pre-service mathematics teacher is better than the field dependent. Also, those with the same cognitive style, which is field independent, but different genders showed different reasoning processes. It was concluded that males have better Statistical Reasoning processes than females, and cognitive style as well as gender affect the reasoning abilities.